Al-Farabi's Concept of Political Welfare - Atsir Ahmad Salman; Muhammad Fajar Pramono; Amir Reza Kusuma; Iqbal Maulana Alfiansyah (al-Afkar, Journal For Islamic Studies, 2024)
The State is formed because of the human need to live together, so it can be concluded that the existence of the State is a necessity in life human. Al-Farabi speaks with physical and spiritual happiness, Sa'adah maddiyah wa ma'nawiyyah, this will not be obtained by people unless they live in a community in an ideal state, al-Madinah al-fadilah. Al-Farabi's political theory of the State boils down to the regulation of the existence of god and devotion to him (theocentric). In contrast to Greek political and statehood theories, al-Farabi later stated that the purpose of statehood was obtain happiness and justice. Al-sa‟adah means happiness, contains the understanding of things that are good to us that are obtained  a person is a gift from Allah SWT alone.